Quality of life, dietary intake and nutritional status of elderly people over 80 years of age institutionalized (Research, Society and Development, 2022)
Associate dietary and water intake with the domains of quality of life (QOL) and nutritional status of elderly older than 80 years long-term residents for the public and private Elderly (ILPIs). Cross-sectional study with 128 elderly, approved by the Ethics and Research Committee under protocol number 2,303,383. A structured questionnaire, International Physical Activity Questionnaire, short version, QoL Assessment Instrument (The World Health Organization Quality of Life - WHOQOL- bref) and 24-hour recall.The nutrients were calculated by dietwin® software. The results were considered significant at a maximum significance level of 5%. Most of the elderly presented with inadequate nutritional status, 19.5% (n=25) underweight and 36% (n=46) overweight. The mean referring to QoL domains was environmental, 32.14 ±12.62, and lowest social 26.70 ±19.87. The higher the protein and lipid intake, the higher the scores of the physical, psychological, social and environmental domains (p=0.006, p=0.012, p=0.046, p=0.012), respectively. And the higher the total calorie consumption, the higher the scores of the psychic, social and environmental domains (p=0.025, p=0.037, p=0.025), respectively. It was concluded that the majority of the elderly were in inadequate nutritional status and the best mean QoL observed was in the environmental domain and lower in the social domain. The consumption of lipids, proteins and total calories, are associated with better QoL scores.